PENGARUH KOMPETENSI PAEDAGOGIK DAN KREATIVITAS GURU TERHADAP HASIL BELAJAR SISWA KELAS IX SMP BARUNAWATI II - Slamet Hamid; Wahyu Utama (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2020)
This study aims to determine the Influence of Paedagogy Competence and Teacher Creativity at SMP Barunawati II. The research method used to analyze is a quantitative calculation method with an associative (correlation) approach, which is to find out the relationship between paedagogic competence and teacher creativity with student learning outcomes. The data collection methods used are questionnaires and interviews. The samples taken were 90 students of class IX and 1 principal. Based on the results of the calculation of the correlation coefficient r = 0.6419 which means that paedagogic competence and teacher creativity have a fairly strong relationship with student learning outcomes. Meanwhile, the results of the coefficient of determination of 41.2% so that it can be concluded that paedagogic competence and teacher creativity affect student learning outcomes by 41.2% and the remaining 58.8% is influenced by other factors. Furthermore, the hypothesis test obtained that the T hitung > T table, which was 7,853 > 1,662, so that Ho was rejected and Ha was accepted, it can be concluded that there is a significant influence between paedagogic competence and teacher creativity on student learning outcomes. From the results of the interview, I can conclude that the father and mother at SMP Barunawati II Jakarta still lack literacy habituation so that there is a lack of insight to develop the material to be taught but the school will continue to strive to accommodate activities that can develop paedagogic competence and teacher creativity at SMP Barunawati II Jakarta, one of which is the holding of technician guidance activities when carrying out the teaching and learning process with invited speakers from outside parties who are experts in their fields, and always opened a discussion room for teachers of SMP Barunawati II to share about the problems of developing paedagogic competencies and teacher creativity when teaching in class